Molecular cloning of a membrane-associated human FK506- and rapamycin-binding protein, FKBP-13. - Jin, Y J (1991)
The 12-kDa FK506-binding protein (FKBP-12) is a cytosolic receptor for the immunosuppressants FK506 and rapamycin. Here we report the molecular cloning and subcellular localization of a 13-kDa FKBP (FKBP-13), which has a 21-amino acid signal peptide and appears to be membrane-associated. Although no internal hydrophobic region, and thus no transmembrane domain, is apparent within the 120 amino acids of mature FKBP-13, a potential endoplasmic reticulum retention sequence (Arg-Thr-Glu-Leu) is found at its C terminus. FKBP-13 has 51% nucleotide sequence identity and 43% amino acid sequence identity to FKBP-12; the N-terminal sequences are divergent, but the 92-amino acid C-terminal sequence of FKBP-13 has 46 identical and 20 related residues when compared with FKBP-12. The conserved residues that comprise the drug binding site and rotamase active site of FKBP-12 are completely conserved in FKBP-13. Therefore, the three-dimensional structures of FKBP-12 and the FKBP-12/FK506 complex are likely to be excellent models of the corresponding FKBP-13 structure.